Examining the Evidence of the Feminization of Poverty in Botswana - Lekobane, Khaufelo Raymond (Journal of Economics and Behavioral Studies, 2015)
Poverty in Botswana is more pronounced in female-headed households (FHHs) especially those residing in rural areas where employment opportunities are limited. Similarly, the proportion of the FHHs to the total poor increased between 2002/03 and 2009/10. However, no study has so far analyzed whether feminization of poverty has occurred. This paper therefore, examines feminization of poverty in Botswana using the 2009/10 Botswana Core Welfare Indicator Survey and the 2002/03 Household Income and Expenditure Survey datasets. The results indicate no evidence of feminization of poverty (at both national and regional levels). However, the results reveal evidence of feminization of poverty amongst the married couples, the widowed, the divorced, the unemployed, those working in own farms and the self-employed. Therefore, public policy should focus on gender sensitive poverty alleviation strategies, with specific focus on the vulnerable FHHs, especially the divorced/separated and the widowed, in order to fully address the feminization of poverty amongst these groups.